THE ISSUE OF RESEARCHING THE HISTORICAL TOPOGRAPHY OF BUKHARA CITY DURING THE SAMANID PERIOD - Baxtishod, Umarov (Journal of Learning on History and Social Sciences, 2025)
Objective: This study examines the historical topography of Bukhara during the Samanid period, a time of significant urban and socio-economic transformation influenced by the Arab Caliphate. It aims to analyze the factors that contributed to the city's rapid development in comparison to other regional centers. Method: The research employs a historical-analytical approach, synthesizing primary sources, archaeological findings, and the works of previous scholars to reconstruct the urban landscape of Bukhara in the ninth and tenth centuries. Results: The findings reveal that Bukhara underwent significant structural and spatial reorganization during the Samanid era, including the expansion of commercial, religious, and administrative centers. The city's architectural advancements and strategic positioning facilitated its emergence as a major cultural and economic hub in Central Asia. Novelty: This study contributes to the discourse on medieval Islamic urbanism by highlighting the unique developmental trajectory of Bukhara under Samanid rule. It synthesizes existing research while offering new insights into the spatial dynamics that distinguished Bukhara from other contemporary cities.